APPLYING AI-TOOLS TO DEVELOP STUDENTS’ LANGUAGE SKILLS - GULYAMOVA , Mavluda Khamitovna (The Lingua Spectrum, 2025)
This study defines the role of artificial intelligence (AI) in teaching foreign languages and its influence on the learning process. It focuses on how AI tools support personalized learning, adaptive teaching, and the development of students’ skills. The author of the article discusses the use of AI tools help both teachers and students. In addition, the study highlights how AI increases student engagement, reduces teachers’ workload, and improves learning outcomes. Possible AI- tools are suggested in order to develop language skills. The results show that effective use of AI can improve teaching quality and support learner-centered education.